Impacts of Covid-19 on households' business, employment and school education: Evidence from household survey in CAREC countries - Dina Azhgaliyeva; Ranjeeta Mishra; Trinh Long; Peter Morgan; Wataru Kodama (Asian Development Bank Institute (ADBI), 2022)
The impacts of the COVID-19 outbreak have heavily affected Central Asia Regional Economic Cooperation (CAREC) member countries, which include Afghanistan, Azerbaijan, Georgia, Kazakhstan, the Kyrgyz Republic, Mongolia, Pakistan, the People's Republic of China (PRC), Tajikistan, Turkmenistan, and Uzbekistan. The COVID-19 crisis and the resulting falls in demand and supply due both to uncertainty and policy measures such as lockdowns, "social distancing," and travel restrictions are having a severe impact on employment and education in CAREC member countries. In order to better understand these impacts, computer-assisted telephone interviews (CATI) of households were conducted in ten countries from the CAREC region (excluding the PRC). This paper estimates the impact of COVID-19 on employment, household business and education in schools in December 2020 compared with June 2020.
Keywords: D14; G51; H12; H84; I10; I24; J6; 330; COVID-19; Central Asia; household survey; school education; employment; family business